2020
DOI: 10.1038/s41467-020-17700-9
|View full text |Cite
|
Sign up to set email alerts
|

Cell-surface receptors enable perception of extracellular cytokinins

Abstract: Cytokinins are mobile multifunctional plant hormones with roles in development and stress resilience. Although their Histidine Kinase receptors are substantially localised to the endoplasmic reticulum, cellular sites of cytokinin perception and importance of spatially heterogeneous cytokinin distribution continue to be debated. Here we show that cytokinin perception by plasma membrane receptors is an effective additional path for cytokinin response. Readout from a Two Component Signalling cytokinin-specific re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 46 publications
4
39
0
Order By: Relevance
“…On the other hand, overexpression of Arabidopsis CYTOKININ OXIDASE/DEHYDROGENASE 1 ( CKX1 ), which encodes a cytokinin‐degrading enzyme that localizes to the ER lumen, leads to a severe phenotype of cytokinin deficiency (Niemann et al ., 2018). Recent studies demonstrated that cytokinins are perceived at the cell surface and at ER‐located receptors (Antoniadi et al ., 2020; Kubiasová et al ., 2020). Both perception sites are important to organize cytokinin signaling, but functional differentiation is still unsolved (Romanov et al ., 2018).…”
Section: Abcg14 and Pup14 Play Different Roles In Cytokinin Transportmentioning
confidence: 99%
“…On the other hand, overexpression of Arabidopsis CYTOKININ OXIDASE/DEHYDROGENASE 1 ( CKX1 ), which encodes a cytokinin‐degrading enzyme that localizes to the ER lumen, leads to a severe phenotype of cytokinin deficiency (Niemann et al ., 2018). Recent studies demonstrated that cytokinins are perceived at the cell surface and at ER‐located receptors (Antoniadi et al ., 2020; Kubiasová et al ., 2020). Both perception sites are important to organize cytokinin signaling, but functional differentiation is still unsolved (Romanov et al ., 2018).…”
Section: Abcg14 and Pup14 Play Different Roles In Cytokinin Transportmentioning
confidence: 99%
“…Moreover, recent experiments confirmed that functional receptors are localised on the plasma membrane [ 253 , 255 ]. While Antoniadi et al [ 253 ] showed that extracellular CKs are capable of CK receptor activation, Zürcher et al [ 255 ] showed the significance of CK removal from the apoplast for proper development. Indeed, there are several apoplast-localised CKX enzymes (e.g., [ 132 , 256 ]).…”
Section: Cytokinin Signallingmentioning
confidence: 99%
“…However, if we accept the premise that the pH of the apoplast is changing, that would also be irrelevant. Further, it is AHK3 that responds strongly to pH change [ 13 ] and it is localised to a lesser extent on the plasma membrane [ 247 , 253 ] as compared to AHK4, which does not respond so strongly to the pH change. The poplar homologues of AHK4 showed, in fact, a negative correlation between t Z binding and pH [ 254 ].…”
Section: Cytokinin Signallingmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytokinin receptors are located in the endoplasmic reticulum as well at the plasma membrane where they perceive cytokinin molecules, followed by the activation of a signal transduction pathway, which is a phosphorelay system that reminds us of the bacterial two-component signaling systems ( Kakimoto, 1996 ; Hwang and Sheen, 2001 ; Schaller et al, 2011 ; Hwang et al, 2012 ; Kieber and Schaller, 2018 ; Romanov et al, 2018 ; Antoniadi et al, 2020 ; Kubiasová et al, 2020 ). Cytokinin is first sensed by a CHASE domain of a histidine kinase receptor (in Arabidopsis, AHK), followed by autophosphorylation of its receiver domain.…”
Section: Introductionmentioning
confidence: 99%